Secure E-Health: Managing Risks to Patient Personal Identity - Amran D., Haryadi; Yuliana, Mike; Soelistijorini, Reni; Sudarsono, Amang (European Scientific Journal, ESJ, 2017)
As we are becoming a digital society, it is very important for us to protect the security of personal identity in any transactions. One of the efforts to maintain the security of personal identity is by unrevealed our data more than necessary. Anonymous credential allows an organization to give a credential to a user. This credential consists of user attribute such as address and date of birth. By using this credential, the user can prove the ownership to the third party without revealing the information that contained in credential information more than necessary. This paper proposes secure ehealth system that focuses on proving protocol to reveal and prove some of the patient attributes while others remain hidden, so the security of personal identity more awake. The experimental results showed that the computational time of each proving protocol less than 1 second.